Hemorrhagic Varicella in a 41-Year-Old Woman with Evans Syndrome : Case Report - Alfina Rahma; Eka Devinta Novi Diana; Frieda; Wibisono Nugraha; Muhammad Eko Irawanto; Moerbono Mochtar (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Varicella is an infection caused by the varicella-zoster virus (VZV) with symptomsof an exanthematous vesicular rash and systemic symptoms. Hemorrhagic varicella commonlyseen in immunocompromised patients. Evans syndrome (ES) is an autoimmune with two or morecytopenias,including autoimmune hemolytic anemia (AIHA) and immune thrombocytopenia (ITP).Case: 41-year-old woman complains of swelling filled with reddish fluid almost all over herbody,sometimes painful and accompanied by fever. Patient also experienced vaginal bleeding resultingin anemia (Hb 8.8 g/DL) and thrombocytopenia (platelets 34,000/uL). Dermatological status of thegeneralized,multiple hemorrhagic vesicles with an erythematous base,partially ruptured. Tzank testrevealed multinucleated giant cells. Patient suffered AIHA and received therapy with methylprednisolone4 mg/day and mycophenolic acid 2x500 mg/day.Conclusion: We report a case of hemorrhagic varicella in a 41-year-old woman with Evan’s syndromewith concurrent features of AIHA and ITP. Dermatological status of the generalized, multiplehemorrhagic vesicles with an erythematous base,some of ruptured with erosions. Tzank test revealedmultinucleated giant cells. Patient was treated with acyclovir 5x800 mg for 7 days,2% salicylic acid and0.5% menthol applied every 12 hours and mupirocin 2% ointment applied twice a day on the erosionarea and clinical improvement was found after 17 days of therapy.